A case study of isolated auroral spots based on DMSP data. (January 2020) - Zhou, Su; Chen, Yuqing; Zhang, Jin
Abstract: This study employed ultraviolet images and particle data to investigate isolated auroral spots away from the Earth's auroral oval. Data from SSUSI (Special Sensor Ultraviolet Spectrographic Imager) and SSJ (Special Sensor J) mounted on the DMSP (Defence Meteorological Satellite Program) spacecraft were examined. The isolated auroral spots were observed by DMSP F16/SSUSI and F17/SSUSI on 29 May 2010 during the recovery phase of a moderate geomagnetic storm with a minimum SYM-H index of −70 nT. The auroral spots were observed between 18:00–21:00 MLT and corotated with the Earth, but stayed almost at the same magnetic latitude (MLAT) of −60°. It is found that the isolated auroral spots were produced mainly by energetic ring current ions at energies above ~10 keV. The enhancement in the electron flux with energy below ~200 eV was also observed for the isolated auroral spots. The MLAT of the electron flux was nearly 2°higher than that for the precipitating ions. Highlights: Isolated auroral spots were observed in the evening sector and corotated with the Earth. The isolated auroral spots were produced mainly by energetic ions with energies above 10 keV. Weak electron precipitation (<200 eV) was observed but the intensity was likely too weak to generate isolated auroral spots.